Performance Development Yamaha Jupiter Z1 Engine on Throtle Body, Muffler and Setting CO - Mirza Yusuf; Putri Rachmawati; Rizky Setiawan (Universitas Muhammadiyah Yogyakarta, 2023)
Yamaha is one of the manufacturers that is concerned about motorsport, this is shown from the various production lines developed. This research focused on Jupiter Z1 Done by changing the manufacturer's standard work system, to improve its performance. This is because the vehicle when in standard conditions is a fuel and power efficient setting, the modifications made are for the stage towards the Roadrace motorcycle racing regulations. There are several regulations covering Mp1 to Mp5 and for mp5 regulations including changes to components that affect to spur motor power, changed components Analysis of Changes in Throttle Body Diameter, Mufler, CO Settings on Yamaha Jupiter Z1. to get maximum exhaust exhaust gas disposal, due to changes in several components that were changed and added, then from these problems made changes to standard data to comply with the Mp 5 roadrace racing regulations. component and data changes include Reamer Throttle body, aftermarket racing mufler replacement and CO (carbon monoxide) data settings. The result is an increase in Horsepower and Torque of 24.3% based on the Dynotest.